Rewiring immune suppression in NSCLC: Roles and plasticity of Tregs and Th17 cells - Zhu, Shasha; Zhou, Ning; Li, Qingling; Liu, Xiaoxing (Frontiers in Immunology, 2025)
Non-small cell lung cancer (NSCLC) exhibits profound immune dysregulation, driven in part by the opposing roles of regulatory T cells (Tregs) and T helper 17 (Th17) cells. Tregs facilitate tumor progression through immune suppression, angiogenesis, and checkpoint engagement, while Th17 cells display dual effects depending on the tumor microenvironment, either promoting anti-tumor responses or enhancing malignancy. Importantly, plasticity between these subsets, orchestrated by cytokines such as TGF-β, IL-6, and IL-1β, allows dynamic interconversion that shapes immune outcomes. This review comprehensively summarizes the differentiation, molecular mechanisms, and functions of Tregs and Th17 cells in NSCLC. We highlight recent advances in targeting the Th17/Treg axis via immune checkpoint inhibitors, Treg depletion, and metabolic reprogramming. Understanding this immunological balance offers promising avenues for restoring anti-tumor immunity and improving therapeutic efficacy in NSCLC patients.